Evaluation of Torsional Vibration on Vertical-type Centrifugal Pump Shaft / Hendri Chandra ... [et al.] - Chandra, Hendri; Luthfi, Muhamad Indra; Lamin, Fauziana; Ariffin, Ahmad Kamal (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A reliable procedure for malfunction detection due to excessive vibration is required especially for equipment that works in a continuous operation. In this paper, an analytical model to describe the vibration level of a verticaltype centrifugal pump shaft was developed. Based on the developed model, vibration characteristics of the pump was simulated. It was found that the pump vibrates at its natural frequency of 15.9 Hz with the amplitude of 0.2903. The tangential forces, as a result of the motor torque, forced the system to vibrate at a higher frequency of 325 Hz with a higher amplitude of 1. Physical vibration measurement revealed that vibration is primarily occurred on the vertical axis, in which point 1 recorded a higher level of vibration as compared to point 2. These procedures allow examination of the vibration level and primary axis of the vibration in the studied pump system for further monitoring application and appropriate maintenance action.